Workstation Evaluation Regarding Ergonomic Awareness and Work-Related Musculoskeletal Disorders Among Coal Mine Workers - Sahito, W. S.; Bazuhair, R. W.; Mimesh, H. (Engineering, Technology & Applied Science Research, 2022)
Mining is often associated with the risk of Work-Related Musculoskeletal Disorders (WRMSDs). Despite being a coal-rich country, Pakistan’s mining sector stays behind in terms of occupational health and safety. Only a few research studies have been conducted on ergonomics in the mining industry. The current study aimed at evaluating workstations for WRMSDs and ergonomic factors among coal mine workers. Survey data were gathered from a total of 103 workers using a structured questionnaire. Information on the incidence of musculoskeletal disorders was obtained using the Standardized Nordic Questionnaire. The questions about ergonomics awareness, workstation, environment, demands, and risks were based on the available literature studies. The association between the incidence of WRMSDs and age was explored using chi-square analysis. The results showed a high rate of uneducated workers with a lack of ergonomics awareness. Back, shoulders, and legs were the most vulnerable body areas to WRMSDs. A significant association between workers’ age and WRMSDs was found. The workers’ opinion towards workstation was at a very low level. The current work conditions were found to have risks of potential hazards and economic losses. Ergonomic interventions are suggested to be developed and implemented to improve workplace conditions.